Aplikasi talfiq dalam resolusi syariah majlis penasihat syariah Bank Negara Malaysia / Mohd Hafiz Jamaludin - Mohd Hafiz , Jamaludin (2016)
Talfiq, though not considered as one source of Islamic law, is frequently used by contemporary scholars. In fact, talfiq was not accepted by majority of classical scholars especially during the era of development of schools of jurisprudence. The period of reformation in Islam (tajdid) in the 20th century has initiated its popularity among the Muslim community particularly with the call to free them from the bondage of rigidness in adopting a particular school of jurisprudence. Talfiq, in fact is an alternative for contemporary scholars who find ijtihad (independent legal reasoning) limited and difficult to provide legal solutions. Yet, there are doubts on whether the ruling derives from talfiq should be treated as a permanent solution or temporary, at least, until the scholars are able to do ijtihad (independent legal reasoning) using recognised sources in the discipline of usul al-fiqh (principles of jurisprudence). As such, this thesis critically studies the concept of talfiq so as to include the scholarly debates between both the proponents and the opponents of talfiq. In order to see the application of this concept in the reality of modern society, this research will refer to the resolutions and decisions passed by The Shariah Advisory Council of Bank Negara Malaysia (SAC). The aim is to analyse to what extent that the use of talfiq is effective in solving issues pertaining to Islamic finance. Due to the global progress in Islamic finance, an analysis on methods used in formulating laws from other selected countries is done to ascertain the applicability of talfiq as the solution of Syariah problems. Hence, data collection includes both the library research and interviews which are further analysed using inductive, deductive and comparative methods. The study reveals that in today’s world, talfiq is highly needed in the process of formulating laws. However, it should be treated as an alternative and not a requirement. Thus, its application should be controlled to avoid negative effects that would arise with it. The study also found that talfiq has been used as an alternative method in formulating rulings among the members of SAC. This is proven through the detailed analysis of its application in numbers of Syariah resolutions.